A case of non-immune hydrops fetalis in an HIV-positive mother - Kumar Chundran, Naveen; Abdul Hadi, Azwanis; Paramanathan, Catherine (Universiti Kuala Lumpur (UniKL), 2025)
Mother-to-child transmission (MTCT) remains the primary route of HIV infection in children, with an estimated 30–40% risk in untreated pregnancies. We report a case of a pregnant woman with a high HIV viral load who developed non-immune hydrops foetalis (NIHF), a rare and life-threatening foetal condition characterized by excessive fluid accumulation in at least two compartments. Ultrasound examinations revealed left ventriculomegaly, cardiomegaly with pericardial effusion, pleural effusion, and ascites with an enlarged spleen, confirming NIHF. Extensive investigations ruled out common infectious and non-infectious causes, raising the possibility of a link between maternal HIV and NIHF. This case highlights the need for further investigation into the potential relationship between maternal HIV, congenital HIV, and NIHF, as well as the importance of early detection and multidisciplinary management in high-risk pregnancies